Investigation Volcanic Land Form and Mapping Landslide Potential at Mount Talang - Diva, Isra Haryati; Irwanto, Usqo; Nizam, Khairul; Annur, Latifa; Sekarjati, Dhanu; Putra, Beben Graha; Safitri, Yuliana; Giovandi, Eggy Arya; Nofrizal, Adenan Yandra; Hanif, Muhammad; Abe, Akina (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The survey geomorphology, it is the one apart of applied geomorphology. In case has done investigation character of geomorphological landscape of Mount Talang and mapping of landslide hazard potential. In this research has used some method, the first field observation and sampling for geomorphology character study were conducted. Second the mapping landslide hazard used method the MAFF Japan where integrating physical field data and spatial data using geographic information system. The results of this study where found some volcanic morphology, volcanic cones, upper slopes, middle slope, lower slopes, foot slope, and volcanic plain. The landslide hazard, where involving sources of observation and sampling for the study of geomorphological characters. From the research has found the landslide hazard in four zone, zone (I) land stable and low hazard potential large 9 ha, zone (II) land enough stable and middle hazard potential large 12.295 ha, zone (III) land less stable and high hazard potential large 1.118 ha, and Zone (IV) land unstable and highest hazard potential 0.1 ha. The typical of geomorphology, morphometry, and land use it has really influence to landslide potential to landslide hazard.